Etoffes de pierre. Techniques d’imitation du textile dans les peintures médiévales du Sud-Ouest de la France - Aurélie Mounier; Floréal Daniel (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Gold, silver and tin play a key role in the iconographic representation of medieval murals or the material reality of objects (wealth of fabrics, armor, etc.). The applied brocade technique, for example, is used to mimic the richness of the tissues of the important characters. Today, these decors have often disappeared and set beneath the adhesive layer. The fluorescence of these binders under ultraviolet light was used to detect the traces of these lesions on about fifteen sites in the south-west of France. The results of analysis highlight the variety and evolution of gilding techniques (in the broad sense) between the eleventh century and the sixteenth century. The choice of type of gilding is oriented by symbolic, economic, technical considerations, the desire to prioritize scenes or for the sake of realism.